2017
DOI: 10.1186/s12887-017-0879-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Glycemic Levels and Treatment Outcome among Critically Ill Children admitted into Emergency Room in Enugu

Abstract: BackgroundCritically ill children are those in need of immediate attention on arrival to an emergency room. The importance of glycemic level measurement as well as maintaining the patency of the airway, effective breathing and circulation cannot be overemphasied. It has been highlighted that the peak hyperglycemia and hypoglycemia predict poor prognosis, longer lengths of hospital stay and higher mortality. The study aims to assess the relationship between glycemic level and treatment outcomes as well as lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…29 Alternatively, it may be a causative factor itself for mortality. 30 Presence of hypo/low glycemia in severely ill child should prompt prioritization of the child, early glucose administration and prevention of further falling of the blood sugar to reduce mortality. The association between low blood glucose and in-hospital mortality as well as 24-hour mortality has been reported from several studies carried out in sub-Saharan Africa.…”
Section: Mortality Risk Factors In Severely Ill Childrenmentioning
confidence: 99%
“…29 Alternatively, it may be a causative factor itself for mortality. 30 Presence of hypo/low glycemia in severely ill child should prompt prioritization of the child, early glucose administration and prevention of further falling of the blood sugar to reduce mortality. The association between low blood glucose and in-hospital mortality as well as 24-hour mortality has been reported from several studies carried out in sub-Saharan Africa.…”
Section: Mortality Risk Factors In Severely Ill Childrenmentioning
confidence: 99%
“…We did not include laboratory values in our study, which represents another of its weaknesses. Multiple studies have shown that hypoglycaemia is associated with increased mortality in critically ill children . In addition, hypercapnia in the ED has been associated with unplanned ICU admission .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that hypoglycaemia is associated with increased mortality in critically ill children. [34][35][36] In addition, hypercapnia in the ED has been associated with unplanned ICU admission. 10 Similar to most paediatric early warning scores, we chose to focus on vital signs and historical patient information to identify high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] In children, the management of brain and non-cranial injuries is equally important in reducing mortality and improving patient prognosis. [ 4 , 5 ] Non-cranial injuries, such as hypercarbia, anemia, and hyperglycemia, lead to systemic inflammation, homeostatic disturbance, and cell apoptosis, subsequently causing a series of secondary adverse events to the human body. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 5 ] Non-cranial injuries, such as hypercarbia, anemia, and hyperglycemia, lead to systemic inflammation, homeostatic disturbance, and cell apoptosis, subsequently causing a series of secondary adverse events to the human body. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%